Unraveling nitrogen metabolism, cold and stress adaptation in polar Bosea sp. PAMC26642 through comparative genome analysis - Khanal, Anamika; Han, So-Ra; Lee, Jun Hyuck; Oh, Tae-Jin (Frontiers in Microbiology, 2025)
Nitrogen metabolism, related genes, and other stress-resistance genes are poorly understood in Bosea strain. To date, most of the research work in Bosea strains has been focused on thiosulfate oxidation and arsenic reduction. This work aimed to better understand and identify genomic features that enable thiosulfate-oxidizing lichen-associated Bosea sp. PAMC26642 from the Arctic region of Svalbard, Norway, to withstand harsh environments. Comparative genomic analysis was performed using various bioinformatics tools to compare Bosea sp. PAMC26642 with other strains of the same genus, emphasizing nitrogen metabolism and stress adaptability. During genomic analysis of Bosea sp. PAMC26642, assimilatory nitrogen metabolic pathway and its associated enzymes such as nitrate reductase, NAD(P)H-nitrite reductase, ferredoxin-nitrite reductase, glutamine synthetase, glutamine synthase, and glutamate dehydrogenase were identified. In addition, carbonic anhydrase, cyanate lyase, and nitronate monooxygenase were also identified. Furthermore, the strain demonstrated nitrate reduction at two different temperatures (15°C and 25°C). Enzymes associated with various stress adaptation pathways, including oxidative stress (superoxide dismutase, catalase, and thiol peroxidase), osmotic stress (OmpR), temperature stress (Csp and Hsp), and heavy metal resistance, were also identified. The average Nucleotide Identity (ANI) value is found to be below the threshold of 94-95%, indicating this bacterium might be a potential new species. This study is very helpful in determining the diversity of thiosulfate-oxidizing nitrate-reducing bacteria, as well as their ability to adapt to extreme environments. These bacteria can be used in the future for environmental, biotechnological, and agricultural purposes, particularly in processes involving sulfur and nitrogen transformation.